The Effect of Vaname Shrimp Pond Waste Disposal (Litopenaeus van-namei) on The Environment and Environmental Law Perspective: a Literatur Review - Dewi, Dewi Fortuna Khairil; Frinaldi, Aldri (Universitas Negeri Padang, 2023)
As a result of observations regarding waste disposal that have been carried out, many shrimp farmers ignore the negative impact of excessive feeding on the environment. Including proper waste management practices, such as processing before discharge into the sea, is often ignored. This research uses a qualitative research method in the form of a literature review (document analysis). The data in this research is information regarding the impacts caused by vaname shrimp waste. The main data sources are obtained through observations and documents from journals or articles that have been published or published. The impact of shrimp pond waste disposal on the environment can cause damage to aquatic ecosystems and environmental pollution. The environmental law perspective regulates legal sanctions for perpetrators of waste disposal from vaname shrimp ponds that damage the environment, such as imprisonment and fines. Several efforts have been made to handle vaname shrimp pond waste for organic fertilizer, waste water treatment installations (IPAL), environmental impact analysis (AMDAL) and supervision from local governments. And the solution that needs to be implemented by business actors is to carry out waste management that meets quality standards, pay attention to AMDA and legal sanctions that can be imposed if you dispose of vaname shrimp pond waste which can damage the environment